Management of pregnancy-related hypertensive disorders in patients infected with SARS CoV-2: pharmacological and clinical issues. Issue 4 (10th September 2020) - Fogacci, Silvia; Fogacci, Federica; Favari, Elda; Toth, Peter P; Borghi, Claudio; Cicero, Arrigo F G
Abstract: Coronavirus-19 disease (COVID-19) continues to spread throughout the world. It is known that among patients with hypertension, diabetes, chronic respiratory disease, or cardiovascular diseases, COVID-19 is associated with greater morbidity and mortality compared with patients without these conditions. This correlation is of great importance in pregnant women affected by COVID-19, since it usually leads to the development of a serious clinical complication. In particular, managing hypertensive disorders in pregnancy can be problematic because antihypertensive medications may interact pharmacologically with drugs used to treat COVID-19. This review focuses on the safety of drug treatment for COVID-19 in pregnant women treated with antihypertensive medication. Several databases were searched to identify relevant literature. A few antihypertensive drugs and antithrombotic treatments are known for having a beneficial effect in the management of hypertension and hypertensive disorders in pregnancy. In this review, we focus on the expected drug–drug interactions with the experimental agents most often used to treat COVID-19. The current indications for the management of hypertension-related disorders in pregnancy maintain their validity, while the risk of pharmacological interaction with the currently tested anti-SARS-CoV-2 medications is relatively low.